The Effect of Silica Dioxide (SiO2) Nanoparticle Coating and Duration of Coffee Immersion on Discoloration of Thermoplastic Nylon Denture Base - Rahmat Hidayat; Helmi Fatchurrahman (Denta Journal Kedokteran Gigi, 2020)
Introduction: Silica dioxide (SiO2) nanoparticle have long been used as a denture base coating. Thermoplastic nylon denture base material is prone to discoloration due to its amide bonds absorb water easily. Meanwhile, coffee contains chlorogenic and tanic acid, which can change the color of denture bases. Purpose: This study was to examine the effect SiO2 coating and duration of coffee immersion on discoloration of thermoplastic nylon denture base. Method: Samples consisted of 24 thermoplastic nylon in square-shaped (30 x 30 x 2 mm), divided into 4 groups (n = 6) which were control (without SiO2 coating) and treatment (with SiO2 coating) groups, which then were immersed in coffee solution for 15 and 30 days. Discoloration test was conducted using spectrophotometer by measuring the delta absorbance of light before and after coffee immersion. Result: The lowest delta absorbance was in the 15-day treatment group (0.019 ± 0.006) and the highest was in the 30-day control group (0.085 ± 0.028). Two-way ANOVA test showed that SiO2 coating and coffee immersion had an effect on discoloration of thermoplastic nylon (p <0.05). Post hoc LSD test showed that there were significant differences between the control and treatment group at 15 and 30 days of coffee immersion (p <0.05). Conclusion: SiO2 as a thermoplastic nylon denture base coating can reduce discoloration by coffee immersion for 15 and 30 days.There were no differences between 15 and 30 days of coffee immersion on thermoplastic nylon’s discoloration in the control and treatment groups.